Direct interaction studies between Aspergillus fumigatus and human immune cells; what have we learned about pathogenicity and host immunity? - Morton, Charles O.; Bouzani, Maria; Loeffler, Juergen; Rogers, Thomas R. (Frontiers in Microbiology, 2012)
Invasive aspergillosis is a significant threat to health and is a major cause of mortality in immunocompromised individuals. Understanding the interaction between the fungus and the immune system is important in determining how the immunocompetent host remain disease free. Several studies examining the direct interaction between Aspergillus fumigatus and purified innate immune cells have been conducted to measure the responses of both the host cells and the pathogen. It has been revealed that innate immune cells have different modes of action ranging from effective fungal killing by neutrophils to the less aggressive response of dendritic cells. Natural-killer cells do not phagocytose the fungus unlike the other innate immune cells mentioned but appear to mediate their antifungal effect through the release of gamma interferon. Transcriptional analysis of A. fumigatus interacting with these cells has indicated that it can adapt to the harsh microenvironment of the phagosome and produces toxins, ribotoxin and gliotoxin, that can induce cell death in the majority of innate immune cells. These data point towards potential novel antifungal treatments including the use of innate immune cells as antifungal vaccines.